Khwadāynāmag The Middle Persian Book of Kings - Hämeen-Anttila, Jaakko (Studies in Persian Cultural History, 2018)
In Khwadāynāmag. The Middle Persian Book of Kings Jaakko Hämeen-Anttila analyses the lost sixth-century historiographical work of the Sasanians, its lost Arabic translations, and the sources of Firdawsī's Shāhnāme. Readership: All interested in Sasanian and early Arabic historiography, Firdawsī's Shāhnāme, and Sasanian history.